Screening of sunflower genotypes for confectionery characters: Screening of sunflower genotypes for confectionery characters - BALPREET KAUR; VINEETA KAILA (Journal of Oilseeds Research, 2020)
Screening of 58 sunflower accessions was done for yield and confectionery parameters for identification of superior confectionery genotypes. The experiment was laid as per augmented design during spring 2019 and data recorded was subjected to statistical analysis for partition of variance components as well as computation of correlation coefficients. Significant differences among entries were observed for all the parameters studied. The superior entries identified were EC-734792, EC-734800, EC-734825 and EC-734844. Among traits specific for confectionery quality significant positive correlation was observed only for 100 seed weight and seed yield per plant. Other confectionery traits such as seed length, seed width, kernel weight and hull content formed a different set.